Saffron for mood improvement in children and adolescents: a narrative review - Gianfranco Trapani; Giulia Maiocco; Alessia Spadavecchia (Hygeia Press di Corridori Marinella, 2022)
Depressive and anxious disorders could be experienced by children and adolescents worldwide and are associated with psychiatric syndromes diagnosed in adulthood. In this context, the COVID-19 outbreak and digital media arising use have worsened mental conditions in the pediatric population. Older adolescents, girls, and patients living with neurodiversity and/or chronic physical conditions are more likely to develop negative mental health outcomes.  Crocus sativus L. (saffron) is a medicinal plant whose most biologically relevant components are two carotenoids (crocin and crocetin) and two apocarotenoids (picrocrocin and safranal). Crocin seems to inhibit the uptake of dopamine and norepinephrine, while safranal inhibits the serotonin reuptake; in vitro and in animal models, crocin also displayed neuroprotective abilities, increasing the intracellular levels of neurotrophic factors. Further studies are required to strengthen these results; however, multiple studies have already demonstrated significant positive effects of saffron on psychiatric disorders - including depression and anxiety in young patients. Saffron administration appears to reduce depression symptoms and to strengthen antidepressant effects of current drugs (fluoxetine), also lowering adverse events of these therapies. Consequently, saffron could have an important role as a complementary therapy for depressive and anxious disorders in children and teenagers.